Gas temperature measurements using wavelength modulation spectroscopy at 1.39 μm - Cai, Tingdong; Tan, Tu; Wang, Guishi; Chen, Weidong; Gao, Xiaoming (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Gas temperature measurements in a combustion system by using wavelength modulation spectroscopy 2f ratio of two selected transitions method were presented for 1.39 μm. Wavelength modulation was performed at 35 kHz, and was superimposed on 500 Hz wavelength scans in order to recover full second-harmonic line shapes. H2O line-pair at 7164.901 cm–1 and 7165.215 cm–1 was selected for this measurement. The criteria of the line-pair selection were discussed. The sensitivity and accuracy of the sensor were demonstrated in a static cell in laboratory (over the temperature range of 400–1000 K, average bias σT ~ 5 K). Burner experiments demonstrate the ability of our system for in situ measurements. The influence caused by variation of total pressure and species concentration in burning gas during combustion was also discussed.
Optica Applicata, Vol. 39, 2009, nr 1, s. 13-29
Keywords: optyka; combustion; gas temperature measurements; wavelength modulation spectroscopy; water vapor